Ye Katolik bťakerestiyan tarik ba Ityopya kaBesu e Abuna Guliyalmo Masyas eska Besu e Abuna Endereyas Garso, 1846-1941 - Antonios Alberto, Abba, OFMCap., 1953- (Addis Ababa, Ethiopia : Capuchin Franciscan Institute of Philosophy and Theology, 1993)
On the history of the Catholic Church in Ethiopia between 1846 and 1941.
Includes bibliographical references (p. 389-397)
In Amharic.